International employment policies : stabilization, adjustment and poverty (ILO GenevaCH, 1986)
Analyses international financial system and describes effects of stabilization and adjustment policies on the poor. Discusses role of OECD countries in the adjustment process of developing countries. Describes the African, Asian, and Latin American experiences with stabilization and adjustment programmes. Reviews effects of stabilization policies on children.
Includes bibliographies